A robust CdS/In2O3 hierarchical heterostructure derived from a metal–organic framework for efficient visible-light photocatalytic hydrogen production. Issue 2 (19th December 2018) - Ren, Jia-Tong; Yuan, Kun; Wu, Ke; Zhou, Liang; Zhang, Ya-Wen
Abstract : CdS/In2 O3 hierarchical nanotubes with intimate and extensive contact between CdS and In2 O3 were synthesized from a MOF and showed huge improvement of visible-light photocatalytic hydrogen production. Abstract : Building sulfide/oxide heterostructure photocatalysts is not only beneficial for the separation and transfer of photo-generated carriers in photocatalytic reactions but also an effective means of broadening the light absorption range of oxides by introducing narrow-bandgap sulfides. However, the construction of highly-efficient sulfide/oxide heterostructures with intimate and extensive contact between different components for visible-light photocatalytic hydrogen production remains a challenge. Herein, a novel sulfide/oxide heterostructure of CdS/In2 O3 hierarchical nanotubes was synthesized starting from a metal–organic framework (MOF). In such a heterostructure, CdS and In2 O3 are integrated by close contact of corresponding small nanoparticles, which is beneficial for the separation and transfer of photo-generated charge carriers. Benefiting from the intimate interface, suitable energy band structure, as well as the inherent advantages of MOFs-derived nanomaterials, the optimal CdS/In2 O3 hierarchical nanotubes showed the best activity in visible-light photocatalytic hydrogen production without any cocatalysts, which was 78.6 times and 16.9 times higher than activities of In2 O3 hierarchical nanotubes and CdS nanoparticles, respectively.